ECC Processor for Design and Implementation of High- Speed RSD - Dharmendar Bochu, ImmadisettyVenkata Prakash, Kale JyothiJeevana (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, an exportable application-particular guideline set elliptic curve cryptography (ECC) processor in view of excess marked digit portrayal is proposed. The processor utilizes broad pipelining methods for Karatsuba– Ofman strategy to accomplish high throughput duplication. Besides, an effective measured snake without correlation and a high throughput secluded divider, which brings about a short data path for expanded recurrence, are executed. The processor bolsters the suggested NIST curve P256 and depends on an expanded NIST decrease plot. The proposed processor performs single point augmentation utilizing focuses in relative directionsin less time.